Glutathione-responsive and -exhausting metal nanomedicines for robust synergistic cancer therapy - Liu, Peng; Hao, Lu; Liu, Min; Hu, Shuo (Frontiers in Bioengineering and Biotechnology, 2023)
Due to their rapid and uncontrolled proliferation, cancer cells are characterized by overexpression of glutathione (GSH), which impairs reactive oxygen species (ROS)-based therapy and weakens the chemotherapeutic agent-induced toxification. Extensive efforts have been made in the past few years to improve therapeutic outcomes by depleting intracellular GSH. Special focus has been given to the anticancer applications of varieties of metal nanomedicines with GSH responsiveness and exhaustion capacity. In this review, we introduce several GSH-responsive and -exhausting metal nanomedicines that can specifically ablate tumors based on the high concentration of intracellular GSH in cancer cells. These include inorganic nanomaterials, metal-organic frameworks (MOFs), and platinum-based nanomaterials. We then discuss in detail the metal nanomedicines that have been extensively applied in synergistic cancer therapy, including chemotherapy, photodynamic therapy (PDT), sonodynamic therapy (SDT), chemodynamic therapy (CDT), ferroptotic therapy, and radiotherapy. Finally, we present the horizons and challenges in the field for future development.